Nation and nurture in seventeenth-century English literature - Trubowitz, Rachel (Oxford : Oxford University Press, 2012)
Rachel Trubowitz connects changing 17th century English views of maternal nurture to the rise of the modern nation, especially between 1603 and 1675.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: Motherhood in literature; Politics in literature; English literature -- 17th century -- History and criticism